Analisis Pemasaran Kain Tenun di Desa Radamata, Kecamatan Kota Tambolaka, Kabupaten Sumba Barat Daya - Karolus Wulla Rato; Rut Sairo; Alfonsus Viyanto Bulu; Samuel Malo; Ogasius Dappa (Institut Nalanda, 2025)
This study aims to analyze the marketing strategy of woven fabrics in Radamata Village, Kota Tambolaka District, Southwest Sumba Regency, and to identify the factors that influence the marketing of these products. Woven fabrics are local products that have great potential as superior commodities in this area, but limited marketing and challenges in distribution often hinder the development of these businesses. The research method used is descriptive with a qualitative and quantitative approach. Data collection was carried out through in-depth interviews with weaving business actors, direct observation in the field, and distributing questionnaires to consumers and woven fabric traders. The results of the study indicate that quality, price, and consumer knowledge of local products are the main determinants in purchasing decisions for woven fabrics. However, there are obstacles in terms of limited distribution and lack of adequate promotion. This study recommends the development of distribution channels, increased promotion through social media, and training for woven fabric craftsmen to increase product competitiveness in a wider market.